TRANSFER OF RIGHTS TO INDIVIDUAL OWNED LAND TO THE COMPANY - Sukirman, Dani Ramdani; Wiryadi, Uyan; Budiman, Anwar (International Peneliti Ekonomi, Sosial dan Teknologi, 2025)
The transfer of land rights refers to the process of moving or shifting land ownership from an individual or a group of people to another individual or group. Based on Article 37 of Government Regulation Number 24 of 1997, the transfer of land rights and ownership rights of a strata title unit, such as through sale, exchange, donation, incorporation into a company, and other legal acts of transfer (except for auctions), can only be officially recorded if proven by a deed created by an authorized Notary Public. Although the regulation doesn't explicitly define 'transfer' and 'transferred,' it clearly outlines the process of transferring land rights or ownership rights of a strata title unit. In practice, many people still buy and sell land without involving a notary or a Notary Public. These transactions often involve only a simple receipt as proof of the sale, without any witnesses. Due to a lack of public awareness about land transfer regulations, many land rights are transferred without any legal validity. This research employs a normative juridical approach, examining laws as they are written (law in books) and as they serve as guidelines for appropriate human behavior. It specifically focuses on the resolution of disputes involving the transfer of individual land ownership to a company, as seen in Supreme Court Decisions Number 852 K/Pdt/2021 and Number 213 K/PDT/2020. These cases highlight the importance of legal certainty when contributing buildings (without the land) as capital to a limited liability company. According to Article 34 of the Company Law, there are specific procedures for contributing capital in forms other than cash. To ensure a clear and legally valid process for contributing immovable property (other than land), a deed of contribution must be created before a Notary Public. This deed serves as official proof of the capital contribution to the limited liability company. Landowners whose land has a building that is contributed as capital to a limited liability company generally only retain ownership rights over the land itself. If there is an agreement between the landowner and the building owner (such as a cooperation agreement, profit-sharing agreement, or lease agreement), all terms, rights, and obligations must be clearly defined to prevent future disputes.